PERENCANAAN PENINGKATAN JALAN LINGKUNGAN KAMPUS UNHI DENGAN AC-BC DAN AC-WC - Wirahaji, Ida Bagus Wirahaji; Cahaya, AAA Cahaya Wardani; Mahapatni, IAP Sri; Indriani, Made Novia; Harta, I Made Harta Wijaya (JURNAL SEWAKA BHAKTI, 2025)
The current environmental road infrastructure on the UNHI campus is still classified as old construction, namely the Macadam Lapen type, which has several weaknesses, namely it is not waterproof and peels easily. This study aims to plan an improvement in the road structure with the latest construction, namely with a hot asphalt mixture of Asphalt Concrete Layer (Laston). This improvement in the road pavement layer is part of the development of the UNHI campus to support the smooth running of academic activities which include analysis of topographic conditions and soil conditions. This research utilizes a descriptive survey approach, collecting data through topographic surveys and soil bearing capacity testing using the Dynamic Cone Penetrometer (DCP). The flexible pavement design method is applied using component analysis. The survey results indicate that the existing road condition comprises 3.00 m wide pavement with light distress and a "lapen" surface type. The proposed pavement structure improvement considers Average Daily Traffic (ADT), soil bearing capacity, and the existing pavement condition. Based on the Bina Marga component analysis method, the overlay design thickness obtained is: AC-WC with a thickness of 4 cm, AC-BC with a thickness of 6 cm, and, for pavement widening and reconstruction, Class A aggregate with a thickness of 15 cm.